Roles of Polysaccharide Gums in the Food and Beverage Industries: A Review - Abdulrazaq, Opeyemi Olabode; Olabode, Ponmile Akeem; Obunadike, Chizoba Victory; Ogunsanmi, Ayomide Oluwaseyi; Muhammed, Zahradeen; Lawal, Isah Abdulshakur; Yakubu, Yussif Yunusah (Jambura Journal of Chemistry, 2024)
Polysaccharides have been used in the food business for a variety of beneficial purposes over the years. The food and beverage businesses must satisfy customer demands while using natural components that perform their technological functions in processed foods. This puts them in increasingly difficult situations. Polysaccharides have numerous useful food uses as stabilizers, thickening agents, and emulsifiers that could be used as additives in the relevant food sectors. In the context of food industry innovation, this review discusses understanding regarding the functions and uses of polysaccharide gums.